2016
DOI: 10.1371/journal.pone.0155070
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Genetic Polymorphism of methylenetetrahydrofolate reductase C677T on Development of Hyperhomocysteinemia and Related Oxidative Changes in Egyptian β-Thalassemia Major Patients

Abstract: Backgroundβ-thalasemia major (β-TM) patients often suffer from various vascular complications together with increased oxidative stress. Hyperhomocysteinemia (Hhcy) has been defined as a risk factor for these complications. Genetic polymorphism of methylenetetrahydrofolate reductase (MTHFR) C677T has been shown to cause Hhcy particularly in individuals with low B-vitamins. However, the status of homocysteine (hcy) in β-TM has not yet been adequately defined.AimTo evaluate the genetic polymorphism of MTHFR C677T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
(58 reference statements)
3
10
0
Order By: Relevance
“…Vitamin B12 and MCV levels were also higher in GG and AG genotypes than in AA genotype. Recent studies had shown that MTHFR 677TT genotype is associated with high Hcy and low folic acid concentrations in β-thalassemia patients [18], and Li concluded that C667T, A1298C, and A66G polymorphisms could elevate the risk of folate deficiency [19]. Lin also reported MA patients with vitamin B12 deficiency and MTHFR (C667T) mutation [20] which was consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Vitamin B12 and MCV levels were also higher in GG and AG genotypes than in AA genotype. Recent studies had shown that MTHFR 677TT genotype is associated with high Hcy and low folic acid concentrations in β-thalassemia patients [18], and Li concluded that C667T, A1298C, and A66G polymorphisms could elevate the risk of folate deficiency [19]. Lin also reported MA patients with vitamin B12 deficiency and MTHFR (C667T) mutation [20] which was consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…For all these reasons, we suggest an antioxidant-rich diet for young women with MTHFR C677T polymorphism. It provides essential nutrients like folate, an important vitamin in the regulation of inflammatory response, cell damage, DNA repair, antioxidant capacity (CAT), Hcy levels, and stability of the MTHFR enzyme [3,16,55,[78][79][80]. Considering that nutrigenetics explains the interaction of gene-nutrients [81,82], our results corroborate with several studies that have reported the importance of personalized nutritional intervention reducing C677T polymorphism effects and preventing many diseases [15,17,27,[83][84][85].…”
Section: Discussionsupporting
confidence: 88%
“…A large number of studies have investigated the association between the rs1801133 polymorphism and CAD risk, as well as the underlying mechanisms, but most of them just focused on homosysteine. It was widely reported that the rs1801133 polymorphism influences the plasma levels of homosysteine in various populations such as Americans [ 25 ], Africans [ 17 , 26 , 27 ], Asians [ 18 , 28 , 29 ], Turkish [ 30 , 31 ] and Brazilians [ 32 ]. In methionine cycle, homocysteine is formed after the removal of adenosine from S-adenosine homocysteine.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have investigated the associations of the rs1801133 polymorphism with CAD and lipid levels. In some of these studies, the T allele of the rs1801133 polymorphism was reported to be associated with an increased risk of CAD [ 10 12 ] and elevated levels of TG [ 13 , 14 ], TC [ 13 15 ] and LDL-C [ 13 16 ], and reduced levels of HDL-C [ 13 , 17 ]. However, the results obtained from other studies did not support these findings [ 18 22 ].…”
Section: Introductionmentioning
confidence: 99%